Proyecto de factibilidad para la creación de una empresa comercializadora de repuestos eléctricos automotrices ubicada en la parroquia de Chaupicruz de la Zona Norte del Distrito Metropolitano de Quito - Rocha Proaño, Patricia Damaris (2013)
In mid 2012, the parish Chaupicruz ceased to exist, because this new parishes were formed. For the development of this project has been taken to the Parish Kennedy, because it is a new parishes that broke away from the former Parish Chaupicruz, in this area there is a large number of mechanical and electromechanical them that mostly provide necessary spare parts to customers, however there are few electrical parts distributors that give them benefits and facilities to the owners of these establishments when purchasing automotive electrical parts.